2018
DOI: 10.1038/s41396-018-0204-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiome development during childhood: an ecological succession influenced by postnatal factors and associated with tooth decay

Abstract: Information on how the oral microbiome develops during early childhood and how external factors influence this ecological process is scarce. We used high-throughput sequencing to characterize bacterial composition in saliva samples collected at 3, 6, 12, 24 months and 7 years of age in 90 longitudinally followed children, for whom clinical, dietary and health data were collected. Bacterial composition patterns changed through time, starting with "early colonizers", including Streptococcus and Veillonella; othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
234
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(269 citation statements)
references
References 101 publications
14
234
1
3
Order By: Relevance
“…As shown here, S. cristatus is clearly capable of disrupting the persistence of S. mutans by producing large amounts of H 2 O 2 and potentially reducing the production of mutacins. Some recent reports have indicated that S. cristatus could be associated with severe early childhood caries; however, more research is needed to corroborate these findings (52,53). Similarly, S. oralis BCC02 appeared highly inhibitory to S. mutans in biofilms, at least partly due to being an efficient H 2 O 2 producer.…”
Section: Discussionmentioning
confidence: 97%
“…As shown here, S. cristatus is clearly capable of disrupting the persistence of S. mutans by producing large amounts of H 2 O 2 and potentially reducing the production of mutacins. Some recent reports have indicated that S. cristatus could be associated with severe early childhood caries; however, more research is needed to corroborate these findings (52,53). Similarly, S. oralis BCC02 appeared highly inhibitory to S. mutans in biofilms, at least partly due to being an efficient H 2 O 2 producer.…”
Section: Discussionmentioning
confidence: 97%
“…Nutrient content is largely stable in mature milk intra‐individually (Garcia et al, ; Hinde et al, ; Power et al, ), and we found no association of nutrient content predicting changes in the microbiome over time. Instead these changes over time may reflect EMT moving different bacteria from the mother's gut to the mammary gland and/or changes in the infant oral microbiome over time (Dzidic et al, ) that changes which bacteria colonize milk through retrograde flow during suction (Ascinar et al, ; Biagi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the composition of SM has been reported to differentiate between dentate and edentulous individuals [28], and full-mouth extraction impacts on SM [29]. Furthermore, SM is affected by dental developmental stages [30,31], and early life development of SM is a coordinated process, influenced by ecological perturbations such as mode of delivery, breastfeeding length and antibiotic treatment [32].…”
Section: The Salivary Microbiota In Oral Healthmentioning
confidence: 99%